Thermophysical properties of fuel clading with various vacuum-arc coatings - Belous, V.A.; Sokolenko, V.I.; Chupikov, A.A.; Kuprin, A.S.; Ledenyov, O.P.; Ovcharenko, V.D. (Вопросы атомной науки и техники, 2019)
The developed research technique for determining emissivity of thin-walled cylindrical samples was used to investigate, in the mode of heat transfer by radiation, thermophysical properties of Zr1Nb fuel cladding samples with different coatings deposited by vacuum-arc method. It has been shown that CrN coating, compared to Zr1Nbbase alloy and Cr coating, can ensure a more effective heat expulsion by radiation in the event of loss-of-coolant accident and high temperature excursion This occurs according to the Stefan-Boltzmann radiation law and due to a higher value of total emissivity for CrN.